EXPLORING THE VALUES OF TAHLILAN TRADITION FOR DEVELOPMENT OF SOCIAL INTERACTION TOPIC IN SOCIAL STUDIES EDUCATION LEARNING (Descriptive Study of Analysis in Gintung Ranjeng Village of Cirebon Regency) - Jaman, Badru (Universitas Pendidikan Indonesia, 2017)
Abstract-The globalization causes Indonesian people prefer to choose foreign cultures compared with preserve their local culture. Beside the local cultured that begin to be threatened, the globalization also affects the decreasing of peoplesâ€™ social attitudes and social behavior, this will certainly vulnerable with the cause of social conflicts. In other aspect. The problems also arise in the social studies education learning which is considered boring, where the material taught does not relate with phenomena of local social and cultural that develop around students. This fact must be sought solution, one of the solutions developed in this research is exploring the values of tahlilan tradition in the social environment of Gintung Ranjeng village, and expected can be used as learning sources that are integrated in the social interaction topic in the social studies education subjects. The findings of this research are : One, the people of Gintung Ranjeng village still hold the tradition of tahlilan with the purpose as one way of their worship to Allah SWT, give console and empathy to abandoned families, efforts to strengthen social relations among society, andÂ prevent the conflict in the community. Two, the interaction pattern of Gintung Ranjeng society is found in the tradition of tahlilan, it can be seen in the activity of â€œatur-aturâ€ and â€œngobengâ€ activities in tahlilan tradition. Three, tahlilan tradition that has a noble value in the social relations, can be used as learning sources in social studies especially on the subject matter social interaction.Â Keywords : Tahlilan Tradition, Social Interaction, and Social Studies